1989
DOI: 10.1002/ajpa.1330800105
|View full text |Cite
|
Sign up to set email alerts
|

Hunting activity and aging among the gidra papuans: A biobehavioral analysis

Abstract: From the individual-based records of hunting practice for 1,633 hr in total and from the hunters' visual acuity and grip strength observed among the Gidra Papuans in lowland Papua New Guinea, this paper aims to analyze the relationship between the hunting activity and aging. The sensori-motor functions determine the range of age in which the individuals act as active or productive hunters: determined to be from the late teen-age years to about 45 years among the present subjects. In this age range, hunting eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…While several studies emphasize the difficulty of hunting (Gurven, Kaplan, and Gutierrez 2006;Ohtsuka 1989;Walker et al 2002), horticulture may also require substantial knowledge and skill to learn proper timing for burning, plot rotation, planting techniques, pest control, and soil management (Conklin 1957). Although the bulk of the calories in horticultural groups comes from carbohydrate staples, such as yams, plantains, and rice, much time is spent engaging in other activities that provide important nutrients as well as prestige, such as hunting and spear fishing (Hames 1989).…”
Section: Wealthmentioning
confidence: 99%
“…While several studies emphasize the difficulty of hunting (Gurven, Kaplan, and Gutierrez 2006;Ohtsuka 1989;Walker et al 2002), horticulture may also require substantial knowledge and skill to learn proper timing for burning, plot rotation, planting techniques, pest control, and soil management (Conklin 1957). Although the bulk of the calories in horticultural groups comes from carbohydrate staples, such as yams, plantains, and rice, much time is spent engaging in other activities that provide important nutrients as well as prestige, such as hunting and spear fishing (Hames 1989).…”
Section: Wealthmentioning
confidence: 99%
“…A number of authors comment that men in their thirties and forties are at their peak in terms of hunting skill (Gubser 1965: 114;Lee 1979: 242). Several studies have shown that men in this age-group have the highest hunting return rates or encounter rates (Ohtsuka 1989;Walker et al 2002). As Gubser (1965: 114) comments, these men may have more children and acquire more responsibility for the community as a whole.…”
Section: Growth and Experiencementioning
confidence: 95%
“…This is indicated by the fact that hunting return rates peak later in life than most other food acquisition activities. Hunting return rate curves peak in the early 30s for the Hiwi , 40 for the Machiguenga and Piro ), early or mid-40s to mid-50s for the Etolo (Dwyer, 1983), 35-45 for the Gidra (Ohtsuka, 1989), 45-50 for the Hadza (Marlowe, 2000) and 37-42 for the Ache.... If, as Kristen Hawkes (2000:65) so aptly put it, "in the long run, big-game hunting is inferior to available alternative strategies for provisioning families," one has to wonder why hunters invest so much of their life, starting already as children, honing these particular skills?…”
Section: Bushman (San) Hunting Successmentioning
confidence: 99%